Articulating Climate Justice in Copenhagen: Antagonism, the Commons, and Solidarity. Issue 3 (31st July 2012) - Chatterton, Paul; Featherstone, David; Routledge, Paul
<x xml:space="preserve">Abstract</x> Abstract: Articulations of climate justice were central to the diverse mobilisations that opposed the Copenhagen Climate Talks in December 2009. This paper contends that articulations of climate justice pointed to the emergence of three co‐constitutive logics: antagonism, the common(s), and solidarity. Firstly, we argue that climate justice involves an antagonistic framing of climate politics that breaks with attempts to construct climate change as a "post‐political" issue. Secondly, we suggest that climate justice involves the formation of pre‐figurative political activity, expressed through acts of commoning. Thirdly, we contend that climate justice politics generates solidarities between differently located struggles and these solidarities have the potential to shift the terms of debate on climate change. Bringing these logics into conversation can develop the significance of climate justice for political practice and strategy. We conclude by considering what is at stake in different articulations of climate justice and tensions in emerging forms of climate politics.